Desperdício de dieta enteral em UTI: análise de modo de falhas e efeitos de danos ao paciente grave - Solfa, Fabiana Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction: This study arose from the need to understand the waste of enteral nutrition in the intensive care unit. Several factors contributed to the waste of enteral feeding and may be intrinsic (gastrointestinal intolerance) or extrinsic to the patient (tests, surgeries), since the diet prescription moment until the end of its administration. Two ways of checking the waste were compared and tested as hypotheses: nurse diary and direct measurement of the residual volume of the bottle. The use of Failure Mode and Effects Analysis methodology in nutritional therapy and the study of diet waste brought originality to the work. Methodology: The waste was verified by quantitative methodology, the volume recorded by the nursing staff and the volume measured on the bottle. Severity scores of patients were also evaluated and compared with enteral nutrition-related variables. The causes of waste could be found at all stages of enteral feeding process, and in this study it was decided by the Failure Mode and Effect Analysis (FMEA) methodology, mapping process, identifying potential risks and evaluating probable damage with score above eight through root cause analysis. Results / Discussion: there was a significant difference between volumes of diet waste according to the nurse diaries and the volume measured on the bottle. The volume registered by the nursing staff was higher than the measured one. This fact may lead to important consequences regarding inappropriate notes once it's about a big volume wasted, according to the records of the nursing staff. As for patient severity scores and variables related to enteral feeding, there were meaningful differences related to sex, age, use of vasoactive drugs and hospitalization time. Thus, the waste was higher among men, not elderly, hospitalized for less than a week (waste per day), without the use of vasoactive drugs. Regarding process failures, most occurred in the period of suspension of the ...

Introdução: O estudo surgiu em razão da necessidade de compreender o desperdício de dieta enteral na unidade de terapia intensiva. Diversos fatores contribuem para o desperdício de dieta enteral, podendo ser intrínsecos (intolerância gastrointestinal) ou extrínsecos ao paciente (exames, cirurgias), desde a prescrição da dieta até o final da sua administração. Duas formas de verificação do desperdício foram comparadas e testadas como hipóteses: a anotação de enfermagem e a medida direta do volume residual do frasco. A utilização da metodologia de Modo de Falhas e Análise de Efeitos na terapia nutricional e o estudo do desperdício da dieta trouxe pioneirismo ao estudo. Metodologia: O desperdício foi verificado por metodologia quantitativa, o volume anotado pela enfermagem e o volume medido no frasco. Foram avaliados também índices de gravidade dos pacientes e comparados com variáveis relacionadas à dieta enteral. As causas do desperdício poderiam ser encontradas em todas as etapas do processo de dieta enteral. Optou-se nesse trabalho, também, pela metodologia da análise do modo de falhas e efeitos (FMEA), mapeando as etapas, identificando os riscos potenciais e avaliando possíveis danos com pontuação acima de oito através da análise de causa raiz. Resultados/ Discussão: Houve diferença significativa em relação aos volumes de dieta desperdiçados segundo a anotação de enfermagem e o volume medido no frasco. O volume anotado pela enfermagem era maior que o medido. Esse fato pode levar a consequências importantes referentes à anotação inadequada por se tratar de um grande volume desperdiçado, segundo a anotação de enfermagem. Quanto aos índices de gravidade do paciente e variáveis referentes à dieta enteral, houve diferença significativa relacionada às variáveis sexo, idade, uso de droga vasoativa e tempo de internação. Assim, o desperdício foi maior entre os homens, não idosos, internados ...
Keywords: Nutrição enteral; Localização de falhas (Engenharia); Desperdicio (Economia); Enfermagem; Enteral feeding